Kebijakan Keimigrasian Indonesia terhadap Negara yang Tidak Memiliki Hubungan Diplomatik: Studi Kasus Israel dan Taiwan - Junior Perdana Sande (Indonesian Perspective, 2022)
This paper provides an analysis of Indonesia’s immigration policies towards Israel and Taiwan, two countries that do not have official diplomatic relations with Indonesia. Immigration policy analysis will focus on the implementation of Indonesia’s selective policy towards foreigners such as applications for entry permits (visas), inspections at Immigration Checkpoints (TPI), supervision of foreigners, and enforcement of Indonesian immigration laws. Through qualitative research methods and descriptive analysis approaches, it can be explained how the concept of national interest is able to influence Indonesia’s decision not to open diplomatic relations with Israel and Taiwan. The differences in background that affect the absence of diplomatic relations have finally contributed to the differences in the policy of granting the Visa of the Republic of Indonesia to citizens of Israel and Taiwan who want to enter the sovereignty territory of the State of Indonesia. The Covid-19 pandemic situation also influenced the policy of granting the visit visa. There are no differences in security enforcement policies at Immigration Checkpoints and immigration control, as well as law enforcement through immigration administration actions between Israeli and Taiwanese citizens and foreigners from other countries.